PERBAIKAN KETERSEDIAAN P DAN EFISIENSI SERAPAN P OLEH TANAMAN BAWANG PREI DENGAN PEMBERIAN ASAM-ASAM ORGANIK DAN CMA PADA TANAH - Machfud Effendy (BUANA SAINS, 2008)
A study on the influence of organic acids and AMF application to availability of P before planting and after harvesting, as well as contribution to P absorption by Leek plant had been done. The treatments consisted of 2 combinations. There were 8 treatments for the first factor, i.e. control, oxalic acid (Ao), C2H2O4.2H2O (0,01 % and 0,02 %), citric acid (As), C6H8O7.H2O 0,01 % and 0,02 %), mix of Ao 0,01 % + As 0,01 %, Ao 0,02 % + As 0,02 %, and inoculation of AMF A.tuberculata. Treatments of the second factor were P-fertilizer and no P-fertilizer. The experiment was arranged in fully randomized design (FRD) with 3 replicates. Results of the study showed that application of organic acids at soil having high potency to P adsorption increased P availability before planting, but AMF inoculation did not give any effect. After harvesting, availability of P was lower than that of the control, nevertheless the treatment of AMF inoculation gave stabile availability of P. Organic acids did not contribute to plant in efficiency of P absorption, moreover at the mix of oxalic acid and citric acid to lower in efficiency